Pengaruh Kepemimpinan, Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Kementerian PPN/BAPPENAS - Priyanti, Aurellia Nina; Silalahi, Edward Efendi; Hasanuddin Hasanuddin (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of leadership, workload, and work environment on employee performance at the Ministry of National Development Planning/Bappenas. The background of this study is based on the phenomenon of leadership imbalance, high workload that affects employee health, and suboptimal work environment conditions, particularly regarding facilities and mobility. The research method used is a quantitative approach with Partial Least Square (PLS) analysis technique through SmartPLS software. The research sample consists of 100 employees selected using a saturated sampling technique. The results show that leadership has a positive and significant effect on employee performance. Workload has a negative but significant effect on employee performance, indicating that as workload increases, performance tends to decrease. The work environment also has a positive and significant effect on employee performance, where adequate facilities and space can increase work productivity.